Konstruksi Vektor Biner Mengandung Gen Hibrid cryIB-cryIAa untuk Transformasi Agrobacterium Tanaman Padi (Oryza sativa L) - Rahmawati, Syamsidah; Slamet-Loedin, Inez H. (Universitas Atma Jaya Yogyakarta, 2004)
This study aimed to obtain binary vectors carrying cryIB-cryIAa hybrid gene suitable for Agrobacterium-mediated transformation of two Indonesian rice cultivars, Rajalele (Javanica) and Cisadane (Indica). Introduction of hybrid Bt toxin, encoded by cryIB-cryIAa hybrid gene with different binding receptor in the insect gut driven by maize ubiquitin promoter, was intended to reduce the possibility of the appearance of stem borer resistant to Bt toxin. A HindIII fragment containing the ubi cryIB-cryIAa hybrid gene was excised from pBKS ubi cryIB-cryIAa and cloned into the HindIII site of binary vector pCAMBIA 1301, 1303, or 1304. Restriction analysis of recombinant plasmids confirmed the insertion of the gene and demonstrated that the gene inserted in two orientations. The recombinant plasmids were transformed into electrocompetent Agrobacterium tumefaciens EHA105 by electroporation. Embryogenic calli of Rajalele and Cisadane were co-cultivated with A. tumefaciens EHA 105 harbouring binary vector pCAMBIA 1301, 1303, or 1304 containing ubi cryIB-cryIAa. GUS histochemical assay revealed that high transformation efficiency (75-100%) on both cultivars were obtained from embryogenic calli transformed with pCAMBIA 1303 or 1304.